ANALISIS ATAS TUHFAH AR-RGHIBN KARYA MUHAMMAD ARSYAD AL-BANJARI - Rusydi, Muhammad (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2010)
This article will analyse Tuhfah ar-Rghibn which was written by Muhammad Arsyad al-Banjari who well-known as one of the central religious figures of the Banjarese society. The first section will describe the contents of Tuhfah ar-Rghibn generally. The second one will analyse the historisity of Tuhfah ar-Rghibn and its methodology. Then, it will be followed by a reflection about the relevance of the methodology of Tuhfah ar-Rghibn for today. Finally, it concludes that Tuhfah ar-Rghibn has theocentrical approach and bayn epistemology. This approach has to re-study to adjust the needs of Banjarese society today.